Tool Tip: Using Google Docs to Encourage Collaborative Learning Outside of Class - McClintic, Katie (Issues in Language Instruction, 2018)
How many times have we, as teachers, waded through a stack of grading, working to provide valuable feedback on homework assignments, only to have students give our comments a cursory glance before stuffing it into their already crammed backpacks? I have seen this time and again in my own classes, always thinking that there has to be a better, more effective way to encourage students to become more reflective about their work. I began to reflect on the assignments I was giving, and the lines of communication between teacher and student that develop through the homework. In the traditional method of pen-on-paper assignments, teachers create the activity as a way to elicit specific practice of a particular skill, opening the dialogue. Then each student completes the work and submits the assignment, thus responding to the initial questions from the teacher. The final step in this communication cycle comes with the teacher providing feedback on the student’s work, thus ending the dialogue. In this structure, the student is responding only to the teacher, attempting to give the teacher the correct answer to the question.